Analisis Yuridis Bentuk Tanggungjawab Sosial Perusahaan Melalui Pendiri Yayasan - Ika Nora; Muhammad Yamin; T. Keizerina Devi A (Iuris Studia: Jurnal Kajian Hukum, 2022)
Foundations that establish various forms of business such as PT according to the above provisions can be justified by law. The foundation that establishes the PT intends to increase the wealth of the foundation which is solely used for the purposes and objectives of the foundation. The type of research used in this research is normative juridical research. The nature of this research is descriptive analytical. The data used is secondary data which can consist of primary legal materials, secondary legal materials, and tertiary legal materials. The results of the discussion in this study are the forms of allocation of CSR funds by companies that are not regulated explicitly and in detail in the legislation, both in the UUPT and in PP No. 47 of 2012, but can be categorized into two categories, namely the form that leads to the implementation of social assistance. and forms of preservation of environmental conditions. The form of marketing related to social activities (cause related marketing) is categorized in the implementation of social assistance. The difference between a company's CSR activities and the form of foundation social activities lies in the form of the applicable legal rules, not in the form in which they are implemented. The forms of activities carried out are almost indistinguishable from one another. The form of the foundation's social activities is part of CSR as well as CSR activities also include social activities and other activities towards the environment. The company's CSR activities that have been carried out by PT. Astra International Tbk, PT. Unilever Indonesia, and PT. Bank Danamon Tbk and PT. Adira Dinamika Multifinance belongs to the scope of CSR as stipulated in the Company Law and does not conflict with the purposes and objectives of UUY because the activity meets the requirements specified in Article 74 of the Company Law, namely that the company is engaged in natural resources, budgeted as company expenses, fulfills the GMS, based on propriety and fairness